2022
DOI: 10.1007/s11606-021-07235-0
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis COVID-19 in Mexico: a Prediction of Severity

Abstract: BACKGROUND: Coronavirus disease 2019 (COVID-19) causes a mild illness in most cases; forecasting COVID-19-associated mortality and the demand for hospital beds and ventilators are crucial for rationing countries' resources. OBJECTIVE: To evaluate factors associated with the severity of COVID-19 in Mexico and to develop and validate a score to predict severity in patients with COVID-19 infection in Mexico. DESIGN: Retrospective cohort. PARTICIPANTS:We included 1,435,316 patients with COVID-19 included before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Overall, our results are in agreement with previous studies in the Mexican population, which reported older age, male sex, hypertension, diabetes, and CKD as risk factors for death and severity in patients with COVID-19 [ 4 , 8 , 45 , 46 , 48 , 52 , 53 , 61 63 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, our results are in agreement with previous studies in the Mexican population, which reported older age, male sex, hypertension, diabetes, and CKD as risk factors for death and severity in patients with COVID-19 [ 4 , 8 , 45 , 46 , 48 , 52 , 53 , 61 63 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, our results are in agreement with previous studies in the Mexican population, which reported older age, male sex, hypertension, diabetes, and CKD as risk factors for death and severity in patients with COVID-19 [4,8,45,46,48,52,53,[61][62][63]. This is of utmost relevance, given that 76% of the Mexican population over 20 years of age is overweight or obese, and the prevalence of obesity increased by 42%, particularly in persons over 50 years of age [64].…”
Section: Comorbidities As Risk Markerssupporting
confidence: 92%
“…The proportion of young people who have lost someone close to them to COVID-19 (37.3%) is relatively high, so it could be said that there is a high proportion of university students who have lost a close person in the present sample. This is because Mexico is one of the countries with the highest mortality due to COVID-19 in the world [ 34 ] and in addition, the age of deaths and infections due to COVID-19 is in the range of 30 and 50 years (65.85%) [ 34 ]. In addition, it is noteworthy that 81% of the sample perceives that the norms to prevent the spread of the virus are not being complied with.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers suggest that about 8% of the general population living in Mexico City got SARS-CoV-2 infection when we conducted the study. Moreover, a recent study indicated that nearly 39% of SARS-CoV-2 positive cases in Mexico were hospitalized due to the COVID-19 severity ( 45 ). These data reflect, to some extent, what we found in our study if we consider the limited number of SARS-CoV-2 detection tests available during that period and the remarkable underestimation of the most severe COVID-19 cases in Mexico.…”
Section: Discussionmentioning
confidence: 99%